Tagged mutations at the Tox1 locus of Cochliobolus heterostrophus by restriction enzyme-mediated integration. - Lu, S (1994)
We have used the restriction enzyme-mediated integration insertional mutagenesis procedure to tag the Tox1 locus in the filamentous Ascomycete Cochliobolus heterostrophus. Mutations at other, unselected, loci were also identified and a high proportion (30-50%) of them were tagged. This procedure may be of general utility for simultaneously mutating and tagging genes in fungi and in other eukaryotes. The Tox1 locus of C. heterostrophus has been defined by Mendelian analysis as a single genetic element that controls production of T toxin, a linear polyketide involved in virulence of the fungus to its host plant, corn. To tag Tox1, protoplasts of a Tox1+ (T-toxin producing) strain were transformed with a linearized, nonhomologous plasmid along with an excess of the restriction enzyme used to linearize the plasmid. Of 1310 transformants recovered, two produced no detectable T toxin in culture or on corn plants. In each of these transformants, the Tox- mutation mapped at Tox1, was tagged with the selectable marker (hygB) on the transforming plasmid, and was tightly linked to the other tagged Tox- mutation. The two mutations, however, represent two different points of plasmid insertion at the Tox1 locus.